Review of: "Cybernetic Based Instruction: an Innovative Learning Model in Digital Age" - Nawarat Sitthimongkolchai (My University, 2023)
The nature of this article is an academic article.As a preliminary study on realizes a review of Cybernetic-Based Instruction, the article is only a descriptive, conceptual framework and does not demonstrate a proven research process or how did the results of the research appear?This article is therefore only the beginning stage of research.Such research should be expanded and conducted to verify the concept whether it is in line with the assumed assumptions or not.In writing the Abstract section, it is clear that this is an article that does not include metrology, research results, and summaries of the results.There is no discussion of the results.But it is considered a good starting point.
Keywords: Technology-Enhanced Education Studies; Online and Blended Learning